An Educational and pedagogical portrait of Bruno Schulz against the background of the portrait-biogram of Franz Joseph I Drohobych Gymnasium - Matorina, Natalia (Poznańskie Studia Slawistyczne, 2024)
The article deals with the relationship between the Drohobych gymnasium named after Franz Joseph and its pupil (and later teacher) Bruno Schulz. The main information and peculiarities of the organization of the educational process in the gymnasium named after Franz Joseph are highlighted; the period of Schulz’s studies in the gymnasium is characterized; the period of Schulz’s teaching and the peculiarities of the relationships between the teacher-Schulz and the pedagogical staff of the gymnasium and its pupils are analyzed; the influence of Schulz on the development and improvement of the educational and cultural space of the Drohobych region are established.